Aplikasi Perhitungan Komponen Pasif Elektronika Berbasis Android - Setiawan, Ade; Saraswati, Sandra Dewi; Bismi, Waeisul (JURIKOM (Jurnal Riset Komputer), 2020)
Increasingly rapid development of mobile phone whether it is the hardware that is used to using a keypad is now a touch screen, and from software are generally still use Symbian OS and Java, now almost everyone is switching to Android OS. This is because the Android OS, has many kinds of advantages in terms of application. Many who use android application which of them is to recite the Qur'an, read a book maulid, learn to cook, order food online even ordered transportation services. They all android phone users should be eased all his daily activities with its gadgets. For this reason the author tries to create android apps that are useful in science learning electronics. Certainly if we discuss the science of electronics, the elaboration widespread, with these authors restrict that application that the author is an application that addresses the basic electronic passive components. The target is this application can be used for elementary, junior high, high school, vocational school, even college course in accordance department. Not only was the application that the author made can be when used for the repair technician electronics devices. With this expected to manufacture android application with the title of the application of knowledge and calculation of passive components basic electronics based on Android can help the learning process in the world of education that certainly from the level of elementary, junior high, high school, vocational and higher education as well as a solution the use of gadgets smarter, precise and instructive